Accuracy of intraoral scanning influenced by different scanning distance and ambient light : A systematic literature review - Thamran, Brandon; Haslinda Z. Tamin; Ariyani (Indonesian Journal of Prosthodontic, 2025)
Background: Intraoral scanning is now widely used in clinical dental practice. The accuracy of impressions obtained using intraoral scanners is a critical factor in the success of fixed prosthodontic restorations. The accuracy of digital intraoral scanning is influenced by scanning distance and ambient lighting conditions. Objectives: This systematic review aims to evaluate the impact of scanning distance and ambient light on the accuracy of intraoral digital impressions. Methods: Following the PRISMA 2020 guidelines, this study conducted a thorough electronic search across PubMed, ScienceDirect, and ProQuest to identify relevant studies.. The Robins I tool assessed the risk of bias in various study types. Data extraction occurred based on predetermined parameters for studying specimens and assessing outcomes. Results: Multiple studies consistently highlight that maintaining an optimal intraoral scanner (IOS) tip distance, typically around 2,5-10 mm, is critical for achieving high-precision digital models, while both closer and farther distances tend to reduce accuracy. Furthermore, extremes in illumination intensity (0 lux and 1500 lux, especially at 7500 K) leading to diminished scan trueness and prolonged scanning times. Conclusion: Scanning distance and ambient lighting conditions affect the accuracy of digital impressions produced using intraoral scanners. Keywords: scanning distance, ambient light, precision, accuracy, intraoral scanners